Words matter: Restoring respect and dignity when referring to individuals with cancer. Issue 13 (9th February 2017) - Ellis, Lee M.; Blanke, Charles D.; Kohn, Elise C.
Abstract : Respecting our patients is the first reassuring step in a long, shared journey during cancer therapy and beyond. The provision of excellent oncologic and medical care in the absence of empathy and respect undermines and compromises the potential value of any intervention.